(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Through the Instrument and Pre-Accession Assistance, European Union provides funding to support the control and eradication of classical swine fever and rabies in seven candidate or potential candidate countries of the Western Balkans, where the main reservoir and vector of rabies is the red fox (Vulpes vulpes). Most of those countries have reinforced measures aiming to control the disease and have initiated oral vaccination programmes against rabies which started in Kosovo in spring 2010. The project was initiated in Macedonia in August 2010 and the first objective was to improve passive surveillance and reporting through enhancing public awareness about the risks of the disease and training for stakeholders. Macedonia is a 25,713 km2 country bordered by four infected countries. In Macedonia, there had been no cases reported since 2000. The first oral vaccination campaigns were implemented in spring and autumn 2011 in the whole country using SADB19 vaccines and aerial distribution. The first case of rabies was detected in July 2011 on a fox in the centre of the country. Eight other cases have been reported in the centre, in the east and in the south parts of Macedonia. Several cases have been isolated at close proximity with Bulgaria and Greece, requiring the implementation of addequate measures in those countries. The last case was recorded in a cat in March 2012. The number of samples and of species analysed in 2011 was significantly increased compared to that of 2009 and 2010. This reflects a higher level of awareness of rabies among hunters, general public and professionals involved in rabies control activities as well as increased quality of the rabies surveillance and monitoring. The efficacy of the campaigns was assessed through monitoring healthy foxes (with active participation of hunters) in all vaccinated areas and revealed a very high percentage of bait uptake (estimated at 91%) and an rabies antibody response of foxes at 59%. The genetic characterization of eight strains isolated in Macedonia has been undertaken to identify rabies variants circulating in the country. The tested isolates were resolved in the East European group with a high nucleotide identity of the nucleoprotein gene found for all isolates, suggesting wildlife movements of rabies in the region. The multi annual rabies control programme will be shortly described (rabies surveillance network, planning, organisation, implementation and evaluation of the campaigns, laboratory investigations) as well as achievements done in the Balkan region. Perspectives for strengthening collaboration with the neighbouring countries for the next years will also be discussed.